Information on the combined hormonal contraceptives (CHC) containing the dienogest + ethinyl estradiol combination (Jeanine®) - A. D. Makatsariya; V. O. Bitsadze; D. V. Blinov; D. I. Korabelnikov (Акушерство, гинекология и репродукция)
In this short communication, the editorial board publishes the information on safety of the combined hormonal contraceptive (CHC) Jeanine®, containing the fixed dose combination of dienogest and ethinyl estradiol. This information has been received from the Russian regulatory authority (Roszdravnadzor) and the manufacturer. According to a metaanalysis of four observational studies, women using the dienogest/ethinyl estradiol fixed dose combination had a higher risk of developing venous thromboembolism (VTE) as compared with women taking the CHCs containing the levonorgestrel/ ethinyl estradiol combination. The estimated risk of developing VTE in women taking the dienogest/ethinyl estradiol combination is 8-11 cases of VTE per 10,000 women per year, while in women taking the CHCs containing levonorgestrel, norethisterone or norgestimate the risk is 5-7 cases of VTE per 10,000 women per year. A patient information leaflet amendment is under consideration by the regulatory authorities. For now, however, hormonal contraceptives containing the dienogest/ethinyl estradiol combination accompanied with the previous version of the instruction are still available in pharmacies. Therefore, when prescribing the combined hormonal contraceptives with dienogest and ethinyl estradiol, the obstetrician-gynecologist should discuss these risks with the woman.